Fat body cells of female reproductive castes of Attini ants (Hymenoptera: Formicidae): An ultrastructural and chemical analysis - Roma, Gislaine Cristina [UNESP]; Bueno, Odair Correa [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2008)
The ultrastructural study on the fat body of gynes (virgin queens) of the basal ant species Cyphomyrmex rimosus and Mycetarotes parallelus and the derived Acromyrmex disciger and Atta laevigata queens showed vesicular rough endoplasmic reticulum, Golgi complex, and mitochondria in trophocytes, Suggesting the involvement of these cells in protein synthesis, in addition to digestive vacuoles associated with the digestion of endocytoscd compounds or rejected cell organelles. Oenocytes, another cell type present in the fat body of these species exhibit mitochondria, digestive vacuoles, and vesicles, indicating a mobilization of compounds by these cells. In A. laevigata, oenocytes also exhibited large storage sites of glycogen, in addition to a well-developed vesicular rough endoplasmic reticulum, suggesting an intensive participation of these cells in protein synthesis. The ultrastructural cytochemistry study also revealed electrodense granules of basic proteins present throughout the cytoplasm of trophocytes. The same was observed in oenocytes, although with smaller amounts of proteins. In the cytoplasm of trophocytes and oenocytes Were also found droplets or electrodense granules of lipids. In ocnocytes of A. disciger and in trophocytes of A. laevigata, lipids were observed in mitochondria, suggesting that this organelle might be a site of synthesis of these compounds. The chemical analysis of lipids revealed that in gynes, the main compounds present in fat body cells were saturated fatty acids, while in queens, saturated as well as unsaturated fatty acids were found. In conclusion, the present study showed that the fat body cells of gynes and queens, in general, maintained the same compounds and original features through the evolution process of the Attini tribe. (C) 2008 Elsevier GmbH. All rights reserved.
Keywords: Trophocyte; Oenocyte; Proteins; Lipids; Ants